Radiopacity and cytotoxicity of Portland cement associated with niobium oxide micro and nanoparticles - Mestieri, Leticia Boldrin [UNESP]; Tanomaru-Filho, Mario [UNESP]; Gomes-Cornelio, Ana Livia [UNESP]; Salles, Loise Pedrosa [UNESP]; Basso Bernardi, Maria Ines; Guerreiro-Tanomaru, Juliane Maria [UNESP] (Univ Sao Paulo Fac Odontologia Bauru, 2014)
Objective: Mineral Trioxide Aggregate (MTA) is composed of Portland Cement (PC) and bismuth oxide (BO). Replacing BO for niobium oxide (NbO) microparticles (Nbp) or nanoparticles (Nbq) may improve radiopacity and bioactivity. The aim of this study was to evaluate the radiopacity and cytotoxicity of the materials: 1) PC; 2) White MTA; 3) PC+30% Nbp; 4) PC+30% Nb eta. Material and Methods: For the radiopacity test, specimens of the different materials were radiographed along an aluminum step-wedge. For cell culture assays, Saos-2 osteoblastic-cells (ATCC HTB-85) were used. Cell viability was evaluated through MTT assay, and bioactivity was assessed by alkaline phosphatase activity assay. Results: The results demonstrated higher radiopacity for MTA, followed by Nb mu and Nb eta, which had similar values. Cell culture analysis showed that PC and PC+NbO associations promoted greater cell viability than MTA. Conclusions: It was concluded that the combination of PC+NbO is a potential alternative for composition of MTA.
Keywords: Silicate cement; Niobium; Nanotechnology